Особливості електролітичного осадження срібних покриттів із кислих тіосечовинно-цитратних розчинів - Смірнова, О. Л.; Пилипенко, О. І.; Бровін, Олександр Юрійович; Ніконов, А. Ю.; Мухін, З. С. (Київський національний університет технологій та дизайну, 2020)
The kinetics of electrode reactions occurring on silver in acidic thiourea-citrate electrolytes has been studied. It was found that thiourea forms stable cationic complexes with Ag+ ions, and citric acid ensures the stability of solutions and promotes the active dissolution of silver anodes. Silver ionization occurs with diffusion control, and cathodic reduction obeys the laws of mixed kinetics. It was shown that the electrolytic deposition of silver proceeds stably with a high current efficiency and gives dense fine-crystalline coatings. The silver deposition rate can be increased by increasing the metal salt content in the electrolyte solution. The introduction of special additives into the electrolyte composition allows increasing the gloss of the coating, its density and fine crystallinity. The use of acidic thiourea-citrate electrolytes significantly reduces the toxicity and danger of the silvering process, reduces material and energy costs for the disposal of wastewater. Silver coatings obtained from acidic thiourea-citrate electrolytes can be used for protective and decorative purposes, as well as for imparting biomedical properties to the surface of metal structures.
Features of the electrolytic deposition of silver coatings from acidic thiourea-citrate solutions
Keywords: електролітичне осадження; срібне покриття; кислі тюсечовинно-цитратні розчіни; silver; thiourea; citric acid; anodic dissolution; cathodic deposition; biomedical applications of silver coatings